The effect of multisensory stimuli on path selection in virtual reality environments - Gonçalves, Guilherme (2019)
Virtual Reality (VR) has as a key feature, the users’ interaction with a virtual environment. Depending on the purpose of a given VR application, it can be essential to use multisensory stimulus without biasing users towards specific actions or decisions in the virtual environment (VE). The goal of the present work is to study if the choice of paths can be influenced by the addition of multisensory stimulus when navigating in a VE using an immersive setup. The awareness of having to take such decisions was also considered. For the purpose, we used a VR game-like application contemplating three levels. Each level was symmetrical and had two possible paths to move to the next level (left or right). For each level, there was a multisensory stimulus on the right path (from a subject orientation): wind, vibration, scent respectively. The sample of the study consisted of 50 participants, and the results showed that none of the multisensory stimuli had a significant impact users’ decision. The users’ awareness of having to decide also did not affect their path. We conclude that multisensory stimuli can be used to raise the credibility of the virtual environments without compromising the users’ decisions.